Constructing Memory, Imagination, and Empathy: A Cognitive Neuroscience Perspective - Gaesser, Brendan (Frontiers in Psychology, 2013)
Studies on memory, imagination, and empathy have largely progressed in isolation. Consequently, humans’ empathic tendencies to care about and help other people are considered independent of our ability to remember and imagine events. Despite this theoretical autonomy, work from across psychology and neuroscience suggests that these cognitive abilities may be linked. In the present paper, I tentatively propose that humans’ ability to vividly imagine specific events (as supported by constructive memory) may facilitate prosocial intentions and behavior. Evidence of a relationship between memory, imagination, and empathy comes from research that shows imagination influences the perceived and actual likelihood an event occurs, improves intergroup relations, and shares a neural basis with memory and empathy. Although many questions remain, this paper outlines a new direction for research that investigates the role of imagination in promoting empathy and prosocial behavior.